Arctic Shipping Development Prospects Evaluation: Nuclear Icebreaker Fleet in the Northern Sea Route. - Khomiakova, Tatiana (Arctic Portal, 2011)
Young researcher Dr.Tatiana Khomiakova, Academy of National Economy, Russia, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.